The Influence of Job Satisfaction and Workload on Employee Performance at PT Citra Riau Sarana - Firman Hidayat; Eko Wiryono; Sumardin Sumardin (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2022)
This research was conducted to determine the effect of job satisfaction and workload on the performance of employees of PT. Citra Riau Sarana. The method used in this research is a descriptive method with a quantitative approach. The object of this research is all employees of PT. Citra Riau Sarana. The research location was conducted at PT. Citra Riau Sarana. The population in this study are employees of PT. Citra Riau Sarana. The samples taken in this study were 47 respondents. The sampling technique in this study was the census method technique with data analysis using the SPSS version 20 program using validity test, reliability test, multiple linear regression, partial test (t test), simultaneous test (F test), coefficient of determination (R2). Multiple regression analysis was used to test the research hypothesis. The results of the study state that the variable workload and job satisfaction have a significant effect partially and simultaneously on employee performance. And it can be concluded that the most dominant workload variable affects employee performance. The coefficient of determination (R2) is 0.771. This means that the variables of job satisfaction and workload simultaneously affect the employee performance variable by 77.1%.